2020
DOI: 10.3390/fermentation6020046
|View full text |Cite
|
Sign up to set email alerts
|

Selenastrum Capricornutum a New Strain of Algae for Biodiesel Production

Abstract: The increasing global demand for biofuels for energy security and to reduce the effects of climate change has created an opportunity to explore new sources of biomass, of which, microalgae is the most promising one. The Laboratory of the Biomass Research Centre (CRB, University of Perugia) is equipped with a photobioreactor that is used to cultivate microalgae under batch conditions. Tests were carried out a temperature of 22 °C and a Photosynthetic Photon Flux Density of 140 µE·m−2·s−1. Cultures were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This system is normally used to cultivate microalgae for the production of protein, fatty acids, pigments, animal feed, and antioxidants in large-scale. Example of microalgal species that have been tested to grow in photobioreactors are Chlorella vulgaris, Chlorella sarokiniana, Arthrospira platensis, Nannochloropsis sp., Phorphyridium cruentum, Selenastrum capricornutum, Haematococcus pluvialis, and Phaeodactylum tricornotum, among others [40,45]. Specifically, photobioreactors allow higher volumetric productivity for the enhanced capture of radiant energy, depending on microalgal strains and scales used.…”
Section: Closed Photobioreactormentioning
confidence: 99%
“…This system is normally used to cultivate microalgae for the production of protein, fatty acids, pigments, animal feed, and antioxidants in large-scale. Example of microalgal species that have been tested to grow in photobioreactors are Chlorella vulgaris, Chlorella sarokiniana, Arthrospira platensis, Nannochloropsis sp., Phorphyridium cruentum, Selenastrum capricornutum, Haematococcus pluvialis, and Phaeodactylum tricornotum, among others [40,45]. Specifically, photobioreactors allow higher volumetric productivity for the enhanced capture of radiant energy, depending on microalgal strains and scales used.…”
Section: Closed Photobioreactormentioning
confidence: 99%
“…Microalgae biomass is typically rich in lipids and can be produced throughout the year [19]. It has been reported that these can produce up to 70% of oils with respect to their dry weight in biomass, compared to other oil crops such as palm (36%), sunflower (40%), and jatropha (28%) [2,20], turning microalgae into a potential source for the production of lipids, and a source of biofuels, biolubricants, or other types of compounds of commercial interest.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in later studies, Knothe added that significantly high amount of myristic acid (C14:0), palmitic acid (C16:0) and palmitoleic acid (C16:1) in an algal lipid will help in meeting the biodiesel standard requirement (Knothe 2011;Knothe 2013;Knothe and Razon 2017). Oils high in oleic acid (C18:1), in particular, have been observed to have a good fuel balance, including ignition quality, combustion heat, cold filter plugging point, oxidative stability, viscosity, and lubricity (Pugliese et al, 2020). As a result, the seven types of FAs stated above, which range from C 14 to C 18 , are referred to as the desirable FAs in this study and are utilized as the reference FAs in establishing the suitability of an algal FAs profile for biodiesel generation.…”
Section: Introductionmentioning
confidence: 99%